Movement Coordination Learning Model: Basic Motoric Skill For Elementary Students - Anggi Setia Lengkana; Entan Saptani; Encep Sudirjo; Mia Rosalina; Dadang Budi Hermawan; Bambang Gatot Sugiarto (JUARA : Jurnal Olahraga, 2022)
This study aims to analyze the effect of the movement coordination learning model on the development of basic motor movements in elementary school-aged children. A total of 50 students became research subjects taken randomly from a total population of 83 people. This study uses an experimental model with "one group pre-test-post test design". The instrument used in this study was the Basic Motor Movement test, which consisted of agility tests, standing long jumps, wall fittings using tennis balls, sprints, flexibility, upright jumps, running coordination, and static balance tests. Data analysis used a statistical approach through SPSS series 20. This study concludes that the Movement Coordination Learning Model affects essential motor development in elementary school-age children. A program recommendation in the future should be planned and prepared for a long-term program to enable children to develop their fundamental motor movements and bring them to the point where they will be ready to improve their abilities at the next level because they have a strong foundation in their psychomotor development phase.